2021
DOI: 10.1111/1745-5871.12485
|View full text |Cite
|
Sign up to set email alerts
|

Sense of place, shopping area evaluation, and shopping behaviour

Abstract: In order to turn the trend of decreasing numbers of visitors in shopping areas, retailers seem to agree on the importance of creating experiences for consumers. Yet sense of place research focusing on shopping areas is limited and has not yet fully explored the extent to which sense of place is related to shopping behaviour within physical shopping areas. In this study, we used the concept of sense of place to study a consumer's experience in inner-city retail environments. The main objective was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Soft-scape, pavements, non-permanent territorial borderlines, social and commercial activities, billboarding, and graffiti are flexible placemaking items. Such a flexible attitude strengthened the sense of place, as defined by Berg et al [38]. On the other hand, formal urban interventions are far from being flexible.…”
Section: Flexibility and Informal Placemakingmentioning
confidence: 92%
“…Soft-scape, pavements, non-permanent territorial borderlines, social and commercial activities, billboarding, and graffiti are flexible placemaking items. Such a flexible attitude strengthened the sense of place, as defined by Berg et al [38]. On the other hand, formal urban interventions are far from being flexible.…”
Section: Flexibility and Informal Placemakingmentioning
confidence: 92%
“…Furthermore, Waxman (2006) utilized an interview approach and found that cleanliness, good scent, sufficient lighting, comfortable seats, and the ability to view exterior activities were the most valued design characteristics in certain coffee shops. Also, Van den Berg et al (2021) found that some physical attributes in a shopping area positively affected the sense of place in the Netherlands. However, they were not explicit about these attributes in their study.…”
Section: 1mentioning
confidence: 98%
“…The sense of place has been used as a social indicator of collaboration between the population and the implementation of new urban policies and plans (e.g., Berg et al, 2021;Hawthorne et al, 2022). According to findings in the scientific literature, the higher the sense of place the greater the resistance to change among the population occupying a given municipality (Tan et al, 2018;Nugroho, & Zhang, 2022).…”
Section: Foundations and Usefulness Of Sense Of Place In The Ecologic...mentioning
confidence: 99%